The influence of non-woven fabric on the initial development of plants growing on difficult-to-sod river embankment surfaces - Piotr Kacorzyk; Mirosław Kasperczyk; Barbara Wiśniowska-Kielian; Wojciech Szewczyk; Andrzej Lepiarczyk; Jacek Strojny; Eliza Wargala (Journal of Water and Land Development)
The aim of the study was to improve the habitat conditions in the initial development of a grass-legume mixture sown in the reconstructed river embankments along the Uszwica River in Kwików and the Vistula River in Kraków, Poland. For this purpose, after sowing the seeds, NPK fertilisation was used, along with the application of a hydrogel to limit the evaporation of water from the soil. Additionally, a non-woven fabric was used to cover the soil. The study was conducted in two stages. In the first stage, polymeric and five biodegradable non-woven fabrics were evaluated in laboratory conditions for their water absorption and retention capabilities. After this assessment, two biodegradable and one polymeric non-woven fabrics were selected for the second stage of field research. A grass- legume mixture consisting of five species of seeds: Lolium perenne L., Poa pratensis L., Festuca rubra L., Festuca arundinacea Schreb. and Trifolium repens L. was used for sowing the embankments. This study takes into account the concept of green economy aimed at addressing the challenges of securing difficult terrains, such as river embankments. The non-woven fabrics used to cover the soil had a positive effect on the initial development of plants, accelerating their emergence, and the degree of soil coverage. After two months post-sowing, the soil surface coverage under the non-woven fabrics was 50% higher compared to areas without such coverage. However, the type of non-woven fabrics and the hydrogel used did not have a significant impact on the initial development of seedlings.